2015
DOI: 10.1002/ppul.23339
|View full text |Cite
|
Sign up to set email alerts
|

Abbreviation modalities of nitrogen multiple‐breath washout tests in school children with obstructed lung disease

Abstract: Cn@TO6 may be suggested as a potential test-shortening endpoint in school children with PCD. In CF, early test termination may reduce measurement power with advancing pulmonary disease, suggesting differences in underlying pathophysiology. Two technically acceptable N2 MBW runs may be sufficient in school children irrespective of diagnosis with CF or PCD. Pediatr Pulmonol. 2016;51:624-632. © 2015 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
32
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 28 publications
5
32
2
Order By: Relevance
“…In our study, agreement of LCI 2.5% and LCI 5% was lower than expected . Yet data from Green et al support our recent findings and question the use of LCI 5% in mild‐to‐moderate lung disease.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…In our study, agreement of LCI 2.5% and LCI 5% was lower than expected . Yet data from Green et al support our recent findings and question the use of LCI 5% in mild‐to‐moderate lung disease.…”
Section: Discussioncontrasting
confidence: 51%
“…Whereas standard LCI is measured at 1/40th of the starting N 2 concentration, abbreviated LCI protocols stop at 1/20th (LCI 2.5% and LCI 5% , respectively). The abbreviated LCI protocol can be applied in patients with CF to shorten the test duration, however, the sensitivity to detect abnormal ventilation inhomogeneity may decrease …”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated the ability of earlier cutoffs of MBW to differentiate health and disease . Our findings are consistent with this earlier work, but also show that LCI 5 is able to capture disease progression and worsening of lung function with increased respiratory symptoms; two important aspects of monitoring patients' health in the clinical setting.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, a cross-talk between human mast cells and TGF-beta1 signaling has been shown. Therefore, it is postulated to use anti-TGF-beta1 signaling against mast cells associated soot toxicity (270). Recently, a novel, potent dual inhibitor (JNJ-10311795; RWJ-355871) of the leukocyte proteases cathepsin G and chymase has been discovered, which also has an anti-inflammatory activity in vivo (271).…”
Section: Possible Therapeutic Interventions To Combat Soot- or Cb-assmentioning
confidence: 99%